Society attitudes towards the Human Rights of homeless people who consume the socalled drug “H”, in the canton of La Libertad (Ecuador) during Covid-19 times - Cevallos Mora , Francia; Guale Sánchez , Andrea; Idrobo Narváez , Ivette; Apolinario Suárez, Gino (Revista Universidad de Guayaquil, 2020)
The global COVID-19 pandemic has deeply transformed our societies in every aspect, highly impacting the lives of people who live under poverty lines. In Ecuador the scenario has worsened for vulnerable populations, even though the legal Constitution establishes the rights of personal integrity, people living on the streets have been left behind. In the Canton La Libertad, the prevalence rate of the consumption of the so-called drug "H" has increased due to the use of it by homeless located in the area of the Seafood Market-Calle Zona H. The need to carry out an analysis of the situation has been identified as a response to the Covid19 health emergency. The study has shown the vulnerability in which they live as well as the lack of access to guarantee of their rights as stated in the Constitution. This has led them to higher poverty rates and unemployment, instability, lack of access to health services, violence, and problematic dependence on alcohol and harmful substances. Therefore, this analysis exposes the need of a comprehensive protection system, with an approach and care to all its particularities, developed in a multidimensional way from the Human Rights perspective.